1995
DOI: 10.2355/isijinternational.35.1170
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development in Controlling the Microstructure and Properties of Low Alloy Steel Weld Metals.

Abstract: (1) where, vTrs; 500/0 fracture appearance of transition temperature. weld metal and inclusions. The amount of AF increases in proportion to the carbon equivalent (CEQ) of weld metal27) as shown in Fig. 9. In other words, it is necessary to ensure appropriate hardenability to obtain good toughness. Harrison considers that supercooling is important for AF formation.11) However, whenheat becomes large, supercoolinput increases and T 800/500 ing decreases, which results in a decrease in AF and an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 1 publication
2
46
0
1
Order By: Relevance
“…The results of other authors 10,17,21,[23][24][25][26][27][28] also show the improvements of mechanical properties in weld metal and HAZ with an increased proportion of acicular ferrite in the microstructure. For instance, Garland and Kirkwood 24,25) found that additions of Mo-Nb or Mo-Ti improved the toughness due to AF formation in the welds of C-Mn steel.…”
Section: ϫ2supporting
confidence: 59%
See 4 more Smart Citations
“…The results of other authors 10,17,21,[23][24][25][26][27][28] also show the improvements of mechanical properties in weld metal and HAZ with an increased proportion of acicular ferrite in the microstructure. For instance, Garland and Kirkwood 24,25) found that additions of Mo-Nb or Mo-Ti improved the toughness due to AF formation in the welds of C-Mn steel.…”
Section: ϫ2supporting
confidence: 59%
“…Similarly, Peng et al 26) found that in submerged arc welds of X-70 line-pipe steel (0.087 % C, 1.5 % Mn and 0.014 % Ti), TiN inclusions nucleated AF which resulted in a high toughness. Even in fire resistant steels, Ohkita and Horii 10) found that AF steels are better than steels with ferrite-pearlite structures with respect to strength and toughness at high temperatures. Also, it has been found that the AF structures can result in superior stress-corrosion-cracking resistance, 29) which is needed in line-pipe steel grades.…”
Section: ϫ2mentioning
confidence: 99%
See 3 more Smart Citations